Assessment of Magnet status and Textbook Outcomes among medicare beneficiaries undergoing hepato‐pancreatic surgery for cancer. Issue 3 (7th May 2021) - Mehta, Rittal; Tsilimigras, Diamantis I.; Pawlik, Timothy M.
Abstract: Background: The relationship between hospital Magnet status recognition and postoperative outcomes following complex cancer surgery remains ill‐defined. We sought to characterize Textbook Outcome (TO) rates among patients undergoing (HP) surgery for cancer in Magnet versus non‐Magnet centers. Methods: Medicare beneficiaries undergoing HP surgery between 2015 and 2017 were identified. The association of postoperative TO (no complications/extended length‐of‐stay/90‐day mortality/90‐day readmission) with Magnet designation was examined after adjusting for competing risk factors. Results: Among 10, 997 patients, 21.3% ( n = 2337) patients underwent surgery at Magnet hospitals (non‐Magnet centers: 78.7%, n = 8660). On multivariable analysis, patients undergoing HP surgery had comparable odds of achieving a TO at Magnet versus non‐Magnet hospitals (hepatectomy: odds ratio [OR]: 1.05, 95% confidence interval [CI]: 0.94–1.17; pancreatectomy—OR: 0.88, 95% CI: 0.74–1.06). Patients treated at hospitals with a high nurse‐to‐bed ratio had higher odds of achieving a TO irrespective of whether they received surgery at Magnet (high vs. low nurse‐to‐bed ratio; OR: 1.38; 95% CI: 1.01–1.89) or non‐Magnet centers (OR: 1.26; 95% CI: 1.10–1.45). Similarly, hospital HP volume was strongly associated with higher odds of TO following HP surgery in both Magnet (Leapfrog compliant vs. noncompliant; OR: 1.24, 95% CI: 1.06–1.44) and non‐Magnet centers (OR: 1.18; 95% CI: 1.11–1.26). Conclusion: Hospital Magnet designation was not an independent factor of superior outcomes after HP surgery. Rather, hospital‐level factors such as nurse‐to‐bed ratio and HP procedural volume drove outcomes.